Online Political Campaigning during the 2014 Regional Elections in Poland - Baranowski, Paweł (2015)
This article is dedicated to the analysis and evaluation of political communication on a regional level. Without any doubt, the Internet revolution affected electoral campaigning on every level. Online campaigning before local elections is often marginalized by political scientists and other scholars researching political marketing. However, the question emerges: are the candidates aware of the possibilities that new media has brought to political communication? Content analysis of all the major online communication tools has allowed the author to analyze the patterns of using websites, official Facebook profiles and Twitter accounts of candidates during the 2014 Lower Silesian Regional assembly elections. The Lower Silesian Voivodeship is among the fastest developing regions in Poland with high Internet penetration rate. Is the Internet campaign treated as a second-class way to communicate with potential voters, or is it perceived as an opportunity to reach electorate online?